MIND MAPPING TO ENHANCE STUDENTS’ WRITING PERFORMANCE - Novi Indah Pradasari; Indra Pratiwi (LET: Linguistics, Literature and English Teaching Journal, 2018)
English is a popular language currently,  it is being taught according to the needs of students. . This situation has contributed to the development of English for Specific Purposes (ESP) (Hutchinson & Waters, 1987). Due to the fact that ESP students have underlying conference repertoire, their language skills are affected by them. Among these skills, writing is considered difficult to get success due to the difficulties faced especially by the EFL students in ESP class. This research is formulated to investigate how mind mapping can enhance students’ writing performance in ESP class. This research implements Collaborative Action Research (CAR). It is done in the form of cycles. It also comprises four steps; planning, acting, developing, and reflecting which are adapted from Mertler’s model (2012). Based on the data analyzed, it could be concluded that mind mapping could be implemented to enhance students’ performance in writing procedure text and solve the problem to generate and organize their ideas before writing. it also brought positive attitude in teaching and learning..